2019
DOI: 10.2217/nnm-2019-0206
|View full text |Cite
|
Sign up to set email alerts
|

Design of Polymeric Nanocapsules to Improve Their lympho-targeting Capacity

Abstract: Aim: To design lympho-targeted nanocarriers with the capacity to enhance the activity of associated drugs/antigens whose target is within the lymphatic system. Materials & methods: Inulin (INU)-based nanocapsules (NCs), negatively charged and positively charged chitosan NCs were prepared by the solvent displacement techniques. The NCs were produced in two sizes: small (70 nm) and medium (170–250 nm). Results: In vitro results indicated that small NCs interacted more efficiently with dendritic cells than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…4c, suggest a preferential interaction of both types of nanoparticles with DCs. This is in accordance with our recent study with polymeric nanocapsules subcutaneously administered to mice, in which we observed a similar trend of preferential interaction with DCs [57]. This preferential interaction was particularly striking in the case of OVA-NP, which may be related to the specialized ability of DCs to recognize different types of antigens.…”
Section: Biodistribution Of Cs:cmβg Nanoparticles In the Lymphatic Systemsupporting
confidence: 93%
See 2 more Smart Citations
“…4c, suggest a preferential interaction of both types of nanoparticles with DCs. This is in accordance with our recent study with polymeric nanocapsules subcutaneously administered to mice, in which we observed a similar trend of preferential interaction with DCs [57]. This preferential interaction was particularly striking in the case of OVA-NP, which may be related to the specialized ability of DCs to recognize different types of antigens.…”
Section: Biodistribution Of Cs:cmβg Nanoparticles In the Lymphatic Systemsupporting
confidence: 93%
“…Popliteal LN were collected 12 h post-administration. It is worth mentioning that at this time point phagocytes are the first cells to encounter the antigen transported by the lymph, so, in line with previous results obtained in our group [57], we expected the main interaction of the particles to be with APCs and not with follicular B cells.…”
Section: Biodistribution Of Cs:cmβg Nanoparticles In the Lymphatic Systemsupporting
confidence: 86%
See 1 more Smart Citation
“…Similarly, the development of drugs capable of targeting specifically SSM might reveal useful to block the IL-1α -STAT3 axis only in these cells and to boost their anti-tumoral properties, in a process of macrophages repolarization 75 . Unfortunately, despite recent studies described compounds capable of localizing differentially in the SCS and in the medullary area of the LN, a therapy able to differentiate specifically macrophage subsets in the LN is still missing 72,76,77 .…”
Section: Discussionmentioning
confidence: 99%
“…These results were in line with previous findings regarding the higher toxicity of pArg NCs than CS NCs [ 5 , 11 ]. On the other hand, INU NCs, without the pArg layer, showed considerably lower toxicities [ 53 , 54 ]. In addition, the higher IMQ content in the INU/pArg NCs could also be related with the increased toxicity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%